The greening of petroleum operations - Islam, Rafiqul 1959-; Chhetri, A. B.; Khan, M. M. (Wiley, 2010)
The Future of Petroleum Operations. This state-of-the-art text analyzes some of the most contentious issues in the energy industry, covering new and greener processes for engineers and scientists and urging them to move petroleum operations closer to sustainability. Although petroleum is still the world's most diverse, efficient, and abundant energy source, there is a growing initiative from global political and industry leaders to "go green," because of climate concerns and high gasoline prices. This book investigates and details how to do that.